Will outlining neonatal near miss events make a change? A hospital based case control study - Ninama, Nittal H.; Shroff, Bhavesh D. (International Journal Of Community Medicine And Public Health, 2019)
Background: In paediatrics and neonatology, the term ‘‘near miss’’ is mostly used in the situation of adverse events during patient care. Another common use of the term is in the perspective of Sudden infant death syndrome (SIDS). No accepted definition of NNM in this setting currently exists. The definition of Neonatal near miss (NNM) used differently, can aid in assessing and improving obstetric and paediatrics practice in different settings. By identifying those neonates that escaped being apprehended as a death statistic, deficiencies in the services rendered to pregnant women may be addressed and this may lead to further improvement in care.1 Methods: The unmatched case control study was conceded in Neonatal intensive care unit (NICU) at Rukamani Chainani Hospital Vadodara. Newborns admitted in NICU, having any one of criteria like birth weight less than 1500, gestational age less than 30 weeks and Apgar score less than 7 at 5 minutes, were defined as Near miss in this study. Results: Neonatal mortality rate was 22 per 1000 live births during study period, whereas neonatal near-miss rate was 87.6 per 1000 live births. In study groups average duration of stay in NICU was 10 days for neonates. Conclusions: There must be a scoring system or calculation of infant mortality index events into the system to identify near miss events which help for the restructuring and improvement of care for pregnant women and newborns.